Water-soluble solid drawing materials
Patent Information
- Application Number
- JP2020211970
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-25
- Filing Date
- 2020-12-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2040-12-22
AI Technical Summary
Existing water-soluble solid drawing materials face issues with strength, leading to chipping, folding, and sticky writing, while also lacking smoothness and even color reproduction, and are prone to breakage under hot and humid conditions.
Incorporating a smectite clay mineral with a methylene blue adsorption amount greater than 100 mmol/100 g, along with a water-soluble polymer and surfactant, to enhance bending strength and solubility, ensuring smooth writing and quick dispersion with a brush.
The solution provides a water-soluble solid drawing material with bending strength comparable to non-water-soluble pencils, preventing breakage and chipping, offering a smooth writing experience and rapid dissolution in water, with improved stability under high humidity.
Smart Images

Figure 00000013_0000 
Figure 00000013_0001
Abstract
Description
Technical Field
[0001] The present invention relates to a water-soluble solid drawing material that, after being drawn on a material such as drawing paper, can be traced with a pen or the like containing water, and the drawn line can be dissolved or dispersed, and a texture similar to that obtained by using watercolor paints can be imparted.
Background Art
[0002] In water-soluble solid drawing materials, the coloring components fixed on the drawing traces need to be dissolved or dispersed in water by adding water. Therefore, it has been proposed to use a water-soluble surfactant as a component of the drawing material. For example, Patent Document 1 discloses a water-soluble solid drawing material containing an ethoxylated aliphatic alcohol such as ethoxylated cetyl alcohol, ethoxylated stearyl alcohol, or ethoxylated cetostearyl alcohol. Patent Document 2 discloses a water-soluble solid drawing material using a polyoxyethylene fatty acid ester together with carboxymethyl cellulose. Further, Patent Document 3 discloses a water-soluble solid drawing material that uses a sorbitan fatty acid ester having an HLB of 1.0 to 8.6 and a polyoxyethylene sorbitan fatty acid ester in combination.
[0003] However, when a water-soluble surfactant is used to impart water solubility or dispersibility to a solid drawing material, there is a problem that the strength of the water-soluble solid drawing material becomes weak, and chipping or breaking during writing is likely to occur. In addition, there is a problem that the writing feeling becomes sticky and is not suitable for detailed drawing.
[0004] As a method for improving the strength of solid drawing materials, Patent Document 4 describes a solid drawing material containing an organic binder, a pigment colorant, and cyclodextrin. The examples disclose a solid drawing material in which polyvinylpyrrolidone is used as the organic binder and cyclodextrin is added, and it is shown that the bending strength of the drawing material is improved. Although watercolor pencil leads are given as an example in the technical field section of Patent Document 4, there are no specific descriptions such as examples showing that the material dissolves or disperses when water is applied to the drawing marks, so it is unclear to what extent the solid drawing material dissolves or disperses in water, and it does not explicitly state that it is possible to achieve both improved strength and solubility or dispersibility in water.
[0005] As a method aimed at improving the strength of water-soluble solid drawing materials while maintaining their solubility or dispersibility in water, Patent Document 5 describes using partially saponified polyvinyl acetate with a degree of saponification of 60 to 80 mol% as a binder, and Patent Document 6 describes using sulfonic acid-modified polyvinyl acetate as a binder. These examples disclose that water-soluble solid drawing materials with excellent water dispersibility, a flexural strength of 30 to 40 MPa, and excellent writing feel can be obtained.
[0006] However, as shown in Patent Documents 5 and 6, simply using water-soluble polymers can result in a lack of smoothness and color coverage when filling in areas during drawing. Furthermore, the solubility or dispersibility in water is still insufficient, and there is a need for solid drawing materials that dissolve or disperse more easily and spread uniformly when tracing the drawing with a water-soaked brush. On the other hand, when drawing outdoors in hot and humid conditions during the summer, water-soluble solid drawing materials tend to absorb moisture, making them prone to breaking, chipping, and crumbling during drawing. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Special Publication No. 2019-510098 [Patent Document 2] Japanese Patent Publication No. 2004-359805 [Patent Document 3] Japanese Patent Publication No. 2018-115322 [Patent Document 4] Japanese Patent Publication No. 2008-088263 [Patent Document 5] Japanese Patent Publication No. 2002-201399 [Patent Document 6] Japanese Patent Publication No. 2009-191215 [Overview of the project] [Problems that the invention aims to solve]
[0008] The present invention aims to provide a water-soluble solid drawing material that has a bending strength comparable to that of so-called medium-hard colored pencil leads that are not water-soluble, and that exhibits a smooth writing feel with excellent color application without breaking or chipping during drawing, without stickiness or snagging, and when the drawing is traced with a water-soaked brush after drawing, the drawn lines quickly dissolve or disperse and spread, thus providing a writing feel and excellent solubility or dispersibility in water. Furthermore, the present invention aims to provide a water-soluble solid drawing material that is less prone to breakage, chipping, or crumbling of the tip due to pen pressure during drawing, even when used under high temperature and high humidity conditions, and that has excellent long-term storage properties. [Means for solving the problem]
[0009] The inventors have found that when a nonionic surfactant such as polyoxyalkylene alkyl ether is used to impart solubility or dispersibility in water to a solid drawing material, simply using a water-soluble polymer such as polyvinyl acetate partial saponified as an adhesive may not provide sufficient strength to the drawing material, resulting in an inferior writing feel. Therefore, in order to solve the aforementioned problems, we conducted thorough research and found that by using a swellable clay mineral in combination with a water-soluble solid drawing material containing a water-soluble polymer and a surfactant, and by using a high molecular weight water-soluble polymer instead of a nonionic surfactant, the long-term storage stability is improved, leading to the present invention.
[0010] In other words, the present invention is as follows:
[0011] (1) A water-soluble solid drawing material characterized by containing a smectite-type clay mineral whose methylene blue adsorption amount, measured by the colorimetric method of JIS Z 2451:2019 6.3, is greater than 100 mmol / 100 g, a coloring agent, a water-soluble polymer, and a surfactant. (2) The water-soluble solid drawing material according to (1), wherein the smectite clay mineral is bentonite. (3) The water-soluble solid drawing material according to (1) or (2), wherein the water-soluble polymer is at least one water-soluble polymer selected from polyvinyl alcohol and polyvinylpyrrolidone. (4) The water-soluble solid drawing material according to any one of (1) to (3), wherein the water-soluble polymer further contains polyethylene glycol having an average molecular weight of 1,000 to 11,000. (5) The water-soluble solid drawing material according to any one of (1) to (4) above, wherein the surfactant is at least one surfactant selected from fatty acid alkali metal salts and nonionic surfactants having an HLB value (Griffin method) of 10 or more and 20 or less. (6) The water-soluble solid drawing material according to any one of (1) to (5) above, wherein the coloring material comprises an opacifying pigment and a coloring pigment. (7) A water-soluble solid drawing material according to any one of (1) to (6) above, further containing wax, wherein the wax consists of a higher fatty acid and an oil or oil derivative. [Effects of the Invention]
[0012] The water-soluble solid drawing material of the present invention has a bending strength comparable to that of non-water-soluble, so-called medium-hard colored pencil leads, and when drawing, it does not break or chip, and exhibits a smooth writing feel with excellent color application without stickiness or snagging. When the drawing is traced with a brush moistened with water after drawing, the drawn lines quickly dissolve or disperse and spread, demonstrating excellent writing feel and water solubility or dispersibility. Furthermore, the water-soluble solid drawing material of the present invention exhibits excellent long-term storage properties, with a small rate of change in flexural strength even when stored under high temperature and high humidity conditions. [Brief explanation of the drawing]
[0013] [Figure 1] This figure shows the relationship between the amount of methylene blue adsorbed by smectite clay minerals and the bending strength of water-soluble solid drawing materials. [Figure 2] This figure shows the rate of change in flexural strength of water-soluble solid drawing materials after storage under high temperature and high humidity conditions. [Modes for carrying out the invention]
[0014] The water-soluble solid drawing material of the present invention is characterized by containing a smectite-type clay mineral, a coloring agent, a water-soluble polymer, and a surfactant.
[0015] [Smectite-type clay minerals] By using smectite-type clay minerals, it is possible to impart flexural strength and a smooth writing feel to water-soluble solid drawing materials, and to rapidly dissolve or disperse the drawing lines in water when water is applied to them. Among smectite-type clay minerals, those with Na-type or K-type interlayer ions have high swelling power and are particularly preferred. In this invention, it is presumed that at least a portion of each component constituting the water-soluble solid drawing material, such as the coloring agent, water-soluble polymer, and surfactant, is incorporated between the layers of smectite-based clay mineral during the manufacturing of the drawing material. In this state, the smectite-based clay mineral has a compact structure due to intermolecular forces between the layered unit crystals, and it is presumed that this contributes to improved strength that cannot be achieved by water-soluble polymer (which functions as an adhesive) alone. Furthermore, it is presumed that during drawing, the fine particles of the smectite-based clay mineral forming the layered structure slide against each other, or that the fine particles of the smectite-based clay mineral themselves slide between the layers, contributing to a smooth writing feel without snagging. When water is applied to the drawing line, it is presumed that the water quickly penetrates between the layers of the smectite-based clay mineral, dissolving the surfactant and water-soluble polymer incorporated between the layers, and dispersing the coloring agent (pigment, etc.), causing the drawing line to spread rapidly.
[0016] Examples of smectite clay minerals include, specifically, bentonite, montmorillonite, hectorite, saponite, stevensite, beidellite, nontronite, sauconite, acid clay, etc. These can be used alone or in appropriate combinations of two or more. Such smectite clay minerals include natural products, purified products of natural products, those with modified swelling properties of natural products, synthetic products, etc.
[0017] Examples of those produced naturally include, for example, as bentonite, Odorite (registered trademark) of Kurosaki Clay Industry Co., Ltd., Odosorb (registered trademark), bentonite of Hojun Co., Ltd., Moistnite-U, Moistnite-S, Moistnite-HC of Kunimine Industries Co., Ltd.; as purified bentonite (products with increased purity of montmorillonite), Kunipia G, Kunipia F, Kunipia G4, Kunipia G10 of Kunimine Industries Co., Ltd.; etc. These are commercially available. Examples of synthetic smectite products include, for example, Smecton SA, Smecton ST, Smecton SWN, Smecton SWF of Kunimine Industries Co., Ltd., etc. These are commercially available.
[0018] When selecting a smectite clay mineral, as an index, it is necessary to select one with a methylene blue adsorption amount measured by the colorimetric method of JIS Z 2451:2019 6.3 greater than 100 mmol / 100 g. The methylene blue adsorption amount is more preferably 120 mmol / 100 g or more, and even more preferably 150 mmol / 100 g or more. When the methylene blue adsorption amount is greater than 100 mmol / 100 g, the water swelling property of the smectite clay mineral becomes good, and when tracing the drawing mark with a pen or the like containing water, the drawing line quickly dissolves or disperses, so a good writing feeling can be obtained. Since the bending strength of the water-soluble solid drawing material is not insufficient, breaks and chips during drawing are unlikely to occur. Also, generally, it is good to use those with a methylene blue adsorption amount of 170 mmol / 100 g or less.
[0019] In the present invention, from the viewpoint of enhancing the water solubility of the water-soluble solid drawing material, bentonite, montmorillonite, hectorite, and stevensite are preferred, and bentonite is particularly preferred. Among bentonites, Na-type bentonite, which contains a large amount of sodium ions in the cations contained between the unit crystal layers, is desirable because it has excellent swelling properties and suspension stability, and a water-soluble solid drawing material with a smooth writing feel and good color development can be obtained. Note that the Na-type bentonite mentioned here may be, for example, Na-substituted bentonite in which calcium ions in Ca-type bentonite are artificially substituted with sodium ions.
[0020] The blending amount of the smectite-based clay mineral is preferably 5 to 50% by mass, more preferably 5 to 20% by mass, and even more preferably 10 to 15% by mass with respect to the total amount of the water-soluble solid drawing material. If the blending amount is 5% by mass or more, the strength as a drawing material will not be insufficient, so there will be no breakage or chipping during drawing, and a good writing feel can be imparted. Also, if the blending amount is 50% by mass or less, the strength of the drawing material will not become too high, so it will not be too hard and the writing feel will not deteriorate. The form of the smectite-based clay mineral used in the present invention is not particularly limited, and for example, powders, granules, scales (flake-like), etc. can be used. Also, the particle size of the smectite-based clay mineral preferably has an average particle size of 10 μm to 300 μm, more preferably 100 μm to 200 μm. The average particle size is measured by the laser diffraction method.
[0021] In the water-soluble solid drawing material of the present invention, from the viewpoint of adjusting the writing feel, it is preferable to blend one or more selected from clay minerals or inorganic substances other than the above-mentioned smectite-based clay mineral as a extender material. Examples of the extender material include talc, kaolin, sericite, mica, silica, calcium carbonate, barium sulfate, etc. The blending amount of the extender material is preferably 25 to 50% by mass, more preferably 30 to 40% by mass with respect to the total amount of the water-soluble solid drawing material. By blending within this range, a good writing taste can be imparted to the water-soluble solid drawing material.
[0022] [Colorant] By using colorants, opacity and color can be imparted to water-soluble solid drawing materials. Examples of conventionally known colorants include inorganic pigments, organic pigments, lake pigments (water-soluble basic dyes and acid dyes made insoluble), pearl pigments, metallic pigments, fluorescent pigments, and water-soluble dyes. These can be used individually or in appropriate combinations of two or more. From the viewpoint of color development, it is preferable to mainly use pigments. Known pigments used in colored pencil leads and the like are preferred in terms of color development and moldability.
[0023] Inorganic pigments include white pigments such as titanium dioxide (titanium white), zinc oxide (zinc oxide), basic lead carbonate (lead white), basic lead sulfate, zinc sulfide, lithopone, titanox, white carbon, and precipitated barium sulfate, as well as carbon black, iron black, ultramarine, red iron oxide, navy blue, titanium black, black iron oxide, yellow iron oxide, red iron oxide, red lead, cinnabar, chromium oxide, cobalt blue, chrome green, titanium yellow, cadmium yellow, cadmium red, cadmium orange, barium yellow, aureolin, molybdate orange, and manganese violet. Inorganic pigments have a limited range of colors but offer subdued tones and excellent weather resistance. Examples of organic pigments include nitro, azo, thioindigo, quinacridone, anthraquinone, and phthalocyanine pigments. Specific examples include: azo pigments such as CIPigment Red 3, CIPigment Red 57:1, CIPigment Red 53:1, CIPigment Yellow 3, CIPigment Yellow 12, and CIPigment Orange 13; thioindigo pigments such as CIPigment Violet 38 and CIPigment Red 88; quinacridone pigments such as CIPigment Red 122, CIPigment Red 206, and CIPigment Red 207; anthraquinone pigments such as CIPigment Red 83 and CIPigment Red 177; and phthalocyanine pigments such as CIPigment Blue 15:1 and CIPigment Green 7. Organic pigments generally have vivid colors, a wide range of colors, excellent coloring power, and good transparency. Examples of lake pigments include First Sky Blue and Methyl Violet. The above pigments can also be used after washing with water, drying, surface treatment, and pH adjustment with an alkali or other pH adjusting agent.
[0024] In particular, it is preferable to use a combination of coloring pigments such as organic pigments, lake pigments, or carbon black, which have good color development properties, and opacifying pigments such as titanium dioxide-based pigments, which have good opacity properties. By using both in combination, the color development on paper can be improved.
[0025] Specific examples of opacifying pigments include titanium dioxide-based pigments, such as white pigments made of titanium dioxide with an average particle size of approximately 0.1 to 0.5 μm. Commercially available products from companies such as Titanium Industries Co., Ltd., Teikoku Chemicals Co., Ltd., Furukawa Mining Co., Ltd., and Ishihara Sangyo Co., Ltd. can be used. Titanium dioxide-based pigments include anatase type (also known as anatase, refractive index 2.45 to 2.55) and rutile type (also known as rutile, refractive index 2.61 to 2.90). The present invention can use either anatase or rutile type. The average particle size is measured by laser diffraction.
[0026] The amount of coloring agent added is preferably 8 to 25% by mass, and more preferably 10 to 20% by mass, relative to the total amount of water-soluble solid drawing material. Furthermore, when using a combination of coloring pigments such as organic pigments, lake pigments, or carbon black with an opacifying pigment, although this varies depending on the desired color of the water-soluble solid drawing material, it is preferable to use both in a mass ratio of 0.01 / 99.99 to 90 / 10, and more preferably 0.05 / 99.95 to 80 / 20.
[0027] [Water-soluble polymer] Water-soluble polymers are used as adhesives to solidify the components of water-soluble solid drawing materials, and by using them in combination with smectite-based clay minerals, the desired strength can be imparted to the water-soluble solid drawing material. Conventionally known water-soluble polymers can be used, such as polyvinyl alcohol, polyvinylpyrrolidone, carboxymethylcellulose, hydroxyethylcellulose, and high molecular weight polyethylene glycol. In this invention, in addition to the above-mentioned water-soluble polymers, polysaccharides that dissolve in cold water can also be used, such as cyclodextrin, guar gum, and gum arabic. These water-soluble polymers can be used individually or in appropriate combinations of two or more. From the viewpoint of water solubility of drawing lines, polyvinyl alcohol is preferred, and polyvinyl alcohol with a degree of saponification of 80 to 90 mol% is more preferred. Furthermore, it is preferable that the water-soluble polymer is at least one water-soluble polymer selected from polyvinyl alcohol and polyvinylpyrrolidone. Moreover, by using polyvinyl alcohol and polyvinylpyrrolidone in combination, a good drawing material can be formed, and the strength of the water-soluble solid drawing material can be maintained even when used under high temperature and high humidity conditions.
[0028] Polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP) are preferably used in a PVA / PVP ratio of 10 / 0 to 2 / 8 (mass ratio), and more preferably in a ratio of 7 / 3 to 4 / 6 (mass ratio). If the amount of polyvinyl alcohol is below the above range, the strength of the water-soluble solid drawing material tends to decrease when used under high temperature and humidity conditions, and if the amount of polyvinylpyrrolidone exceeds the above range, the moldability decreases, making it impossible to obtain a good water-soluble solid drawing material.
[0029] In this invention, it is preferable to use high molecular weight polyethylene glycol to prevent the lead from crumbling during writing, even when the water-soluble solid drawing material is used under high temperature and high humidity conditions. By incorporating high molecular weight polyethylene glycol, the problem of the tip of the water-soluble solid drawing material breaking, chipping, or crumbling during drawing under high temperature and high humidity conditions can be resolved.
[0030] The average molecular weight of high molecular weight polyethylene glycol is preferably 1,000 to 11,000, more preferably 2,000 to 11,000, and particularly preferably 3,000 to 9,000. If the average molecular weight is less than 1,000, the moldability may be poor, and the long-term storage stability under high temperature and humidity conditions may also be poor. If the average molecular weight exceeds 11,000, the moldability and water solubility may be poor. Furthermore, polyethylene glycol with a freezing point (°C) of 50°C or higher (i.e., an average molecular weight of 2,000 or higher) is preferred in terms of its excellent long-term storage stability under high temperature and humidity conditions. The average molecular weight of polyethylene glycol used is that specified in the 2006 Japanese Standards for Quasi-Drug Ingredients (hereinafter the same applies).
[0031] Specifically, examples include polyethylene glycol 1000 (average molecular weight 1,000), polyethylene glycol 1540 (average molecular weight 1,450-1,540), polyethylene glycol 2000 (average molecular weight 2,000), polyethylene glycol 4000 (average molecular weight 3,100-3,400), polyethylene glycol 6000 (average molecular weight 8,300-8,800), polyethylene glycol 11000 (average molecular weight 11,000), etc. Depending on the product, a # may be added between polyethylene glycol and the numerical value, such as polyethylene glycol #2000. Commercially available polyethylene glycol can be used, and those sold by NOF Corporation, Daiichi Kogyo Seiyaku Co., Ltd., Sanyo Chemical Industries, Ltd., etc. can be used.
[0032] The amount of water-soluble polymer (other than high molecular weight polyethylene glycol) added is preferably 5 to 15% by mass, and more preferably 7 to 12% by mass, relative to the total amount of water-soluble solid drawing material. If it is 5% by mass or more, the desired strength can be imparted to the water-soluble solid drawing material, and if it is 15% by mass or less, the drawing material will not become too hard and the writing feel will not deteriorate. Furthermore, the amount of high molecular weight polyethylene glycol added is preferably 5 to 20% by mass, more preferably 5 to 15% by mass, and particularly preferably 8 to 12% by mass, relative to the total amount of the water-soluble solid drawing material, separate from the amount of the water-soluble polymer mentioned above. If the amount of polyethylene glycol is 5% by mass or more, the water solubility and writing properties of the water-soluble solid drawing material will be good, and the bending strength under high temperature and high humidity conditions will be maintained. If the amount is 20% by mass or less, the water-soluble solid drawing material will not become too soft, and the desired strength (hardness) will be maintained.
[0033] In this invention, polyethylene glycol has water solubility but low hygroscopicity, making it less susceptible to humidity changes. Furthermore, its molecular structure is compatible with smectite-type clay minerals (bentonite), and it is easily incorporated into the interlayer. Therefore, it is presumed that the polyethylene glycol incorporated into the bentonite contributes to preventing changes in strength even in high-temperature and high-humidity environments. Additionally, polyvinylpyrrolidone has high hygroscopicity, but it is compatible with smectite-type clay minerals (bentonite), and its inherent properties are harder than polyvinyl alcohol, so it is presumed that changes in strength are less likely to occur.
[0034] [Surfactants] By using surfactants, water-soluble solid drawing materials can be imparted with solubility or dispersibility in water. Water-soluble surfactants are preferred as surfactants because they can enhance the solubility and dispersibility of water-soluble solid drawing materials. Conventional surfactants can be used, including, for example, anionic surfactants such as primary or secondary alkyl sulfate salts, alkyl ether sulfate salts, α-olefin sulfonates, alkyl sulfonates, α-sulfo fatty acid salts, and higher fatty acid salts; nonionic surfactants such as alkyl polyoxyethylene ethers, alkylphenyl polyoxyethylene ethers, styrene-phenyl polyoxyethylene ethers, fatty acid polyoxyethylene esters, fatty acid polyoxyethylene sorbitan esters, fatty acid polyoxyethylene glycerin esters, and sucrose fatty acid esters; or cationic surfactants. These can be used individually or in appropriate combinations of two or more.
[0035] In the water-soluble solid drawing material of the present invention, it is preferable to use an anionic surfactant alone or in combination with a nonionic surfactant. Anionic surfactants have good water solubility and can impart a smooth writing feel. Nonionic surfactants have good wettability with smectite-type clay minerals and can improve the flexural strength of the water-soluble solid drawing material. From the standpoint of providing both the lightness of writing when drawing with the water-soluble solid drawing material on materials such as drawing paper and the lightness of writing when dissolving or dispersing the drawing lines, it is preferable to use anionic surfactants and nonionic surfactants in a combination of 1 / 9 to 9 / 1 (mass ratio), more preferably 3 / 7 to 7 / 3 (mass ratio), and even more preferably 4 / 6 to 6 / 4 (mass ratio). Furthermore, from the standpoint of improving long-term storage stability under high temperature and high humidity conditions, it is preferable to use anionic surfactant alone.
[0036] The hydrophobic group in anionic surfactants can be appropriately selected from linear or branched alkyl or alkenyl groups having 10 to 18 carbon atoms. Among anionic surfactants, alkali metal salts of higher fatty acids are preferred due to their excellent water solubility and writing properties. Specific examples include alkali metal (Na, K) salts of fatty acids such as lauric acid soap, myristic acid soap, palmitic acid soap, stearic acid soap, oleic acid soap, beef tallow fatty acid soap, and coconut fatty acid soap.
[0037] Nonionic surfactants are preferably HLB values between 10 and 20 from the viewpoint of flexural strength and water solubility of the drawn lines. If the HLB value of a nonionic surfactant is within the above range, the drawn lines tend to disintegrate when water is added. Here, the HLB value is defined by the Griffin formula shown below. HLB = 20 × Mw / M (In the formula, M is the molecular weight of the nonionic surfactant, and Mw is the formula weight of the hydrophilic portion of the nonionic surfactant.) If the hydrophilic group consists only of a POE group, HLB = E / 5 (In the formula, E is the weight fraction of the oxyethylene group.) In the case of polyhydric alcohols and fatty acid esters, HLB = 20(1 - S / A) (In the formula, S is the saponification value of the ester, and A is the acid value of the fatty acid.) If it is difficult to determine a clear saponification value, HLB = (E + P) / 5 (In the formula, P is the weight fraction of the polyhydric alcohol.)
[0038] In ether-type nonionic surfactants, the hydrophobic group can be selected from linear or branched alkyl or alkenyl groups having 10 to 18 carbon atoms, phenyl groups having substituents with 5 to 18 carbon atoms, and the like. Preferred specific examples include polyoxyethylene decyl ether, polyoxyethylene lauryl ether, polyoxyethylene myristyl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene cetostearyl ether, polyoxyethylene polyoxypropylene decyl ether, polyoxyethylene polyoxypropylene lauryl ether, polyoxyethylene polyoxypropylene stearyl ether, and polyoxyethylene styrene-phenyl ether. Polyoxyethylene alkyl ethers, in particular, exhibit excellent water solubility and writing feel.
[0039] In ester-type nonionic surfactants, the fatty acid ester portion can be appropriately selected from mono, di, or triesters of any fatty acid having a linear or branched alkyl or alkenyl group with 10 to 18 carbon atoms, as long as the water solubility of the surfactant is not impaired. Preferred specific examples include, for example, fatty acid polyoxyethylene sorbitan esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan sesquilaurate, polyoxyethylene sorbitan dilaurate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan sesquioleate, polyoxyethylene sorbitan dioleate, and polyoxyethylene sorbitan monostearate; fatty acid polyoxyethylene polyhydric alcohol esters such as polyoxyethylene monoglyceryl laurate, polyoxyethylene monoglyceryl isostearate, and polyoxyethylene monoglyceryl stearate; and sucrose fatty acid esters such as sucrose laurate, sucrose myristic acid, sucrose palmitate, sucrose stearate, and sucrose oleic acid. In particular, fatty acid polyoxyethylene glycerol esters offer excellent water solubility and writing feel.
[0040] The amount of surfactant added is preferably 10 to 30% by mass, and more preferably 10 to 25% by mass, relative to the total amount of water-soluble solid drawing material. If it is 10% by mass or more, good solubility or dispersibility in water can be imparted to the water-soluble solid drawing material, and if it is 30% by mass or less, stickiness when writing can be suppressed.
[0041] [wax] The water-soluble solid drawing material of the present invention may further contain wax in addition to the above components. By using wax, the writing feel of the water-soluble solid drawing material can be improved. Examples of waxes include higher fatty acids such as stearic acid and palmitic acid, higher alcohols or their esters, oils and fats or oil derivatives such as hydrogenated castor oil, petroleum-based waxes such as paraffin wax and microcrystalline wax, plant-based waxes such as carnauba wax and wood wax, animal-based waxes such as beeswax and lanolin, and synthetic waxes such as polyethylene wax. These can be used individually or in appropriate combinations of two or more.
[0042] The amount of wax added is preferably 3 to 15% by mass, and more preferably 5 to 10% by mass, relative to the total amount of water-soluble solid drawing material. If the amount is 3% by mass or more, the smoothness of the writing feel will not decrease, and if it is 15% by mass or less, it will not cause a decrease in moldability or uneven coating due to bleeding out over time.
[0043] In addition to the above-mentioned components, the water-soluble solid drawing material of the present invention may optionally contain antioxidants, ultraviolet absorbers, fungicides, preservatives, antibacterial agents, fragrances, etc., to the extent that they do not impair the effects of the present invention.
[0044] Methods for producing the water-soluble solid drawing material of the present invention include, for example, adding an appropriate amount of water to each of the above components, heating, mixing, and stirring the mixture in a Henschel mixer or kneader, and then uniformly kneading it with a three-roller or the like. The mixture is then injected, extruded, or poured into a mold to form a wire of a desired core thickness, and then dried.
[0045] The water-soluble solid drawing material of the present invention can be widely used as a drawing material for various purposes in various forms, and in particular, when formed into a rod shape with a diameter of about 0.5 to 5 mm (preferably about 1 to 4 mm), it is suitable as a lead for so-called watercolor pencils. [Examples]
[0046] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0047] The method for measuring the physical properties of the components used in the examples and the method for evaluating the obtained water-soluble solid drawing material are as follows.
[0048] <Amount of methylene blue adsorbed by smectite-type clay minerals> In accordance with JIS Z 2451:2019 6.2.4a) boiling method and 6.3 colorimetric method, methylene blue was gradually added to a suspension of the sample (smectite-type clay mineral such as bentonite) dispersed in water, allowing it to be adsorbed onto the sample. The amount of adsorbed material was calculated from the amount of methylene blue added when adsorption was no longer possible.
[0049] <Bending strength and rate of change of bending strength of water-soluble solid drawing materials> In accordance with JIS S 6006, the bending strength (P1) was measured at a temperature of 23°C and a humidity of 60% RH using a three-point bending test (support distance 60 mm, load application speed 10 mm / min). Using the same method, the bending strength (P2) was measured after being left for three weeks at a temperature of 40°C and a humidity of 60% RH, and the rate of change in bending strength was calculated using the following formula. Change in bending strength (%) = {(P1-P2) / P1} × 100
[0050] <Water solubility of water-soluble solid drawing materials> The evaluation was conducted according to the following procedure. 1) Create a 3cm x 3cm frame on drawing paper, and fill in the central 2cm x 2cm area with water-soluble solid drawing material from all four directions (top, bottom, left, and right). 2) Trace the 3cm x 3cm frame with a water-soaked brush, filling in vertically and horizontally from the edges of the frame to dissolve the drawing lines. 3) Count the number of times the brush was used until the drawing lines dissolved and the color tone within the 3cm x 3cm frame became uniform, and evaluate according to the criteria shown in Table 1 below.
[0051] [Table 1]
[0052] <Writing feel of water-soluble solid drawing material> The writing feel of the water-soluble solid drawing material described above during the filling process (step 1) was evaluated sensorily and assessed according to the criteria shown in Table 2 below.
[0053] [Table 2]
[0054] (Examples 1-17, Comparative Examples 1-3) The ingredients and quantities (mass%) shown in Table 3 were placed in a Henschel mixer, an appropriate amount of water was added, and the mixture was stirred and mixed at 70-95°C. After further kneading with a three-roller at 30-70°C, the mixture was formed into thin rods using an extrusion molding machine to produce wire cores. After that, they were thoroughly dried to obtain red wooden colored pencil leads (water-soluble solid drawing material) with a length of 180 mm and a diameter of 3 mm. The obtained water-soluble solid drawing material was subjected to flexural strength measurements, water solubility, and evaluation of writing feel. The results are shown in Table 3. In Table 3, "MB" is an abbreviation for methylene blue adsorption amount (unit: mmol / 100g).
[0055] [Table 3]
[0056] The results in Table 3 and Figure 1 show that the water-soluble solid drawing material of the present invention, which contains a smectite-type clay mineral with a methylene blue adsorption capacity greater than 100 mmol / 100g, exhibits significantly superior flexural strength compared to materials without smectite-type clay minerals (Comparative Example 1) and materials with a methylene blue adsorption capacity of 100 mmol / 100g or less (Comparative Examples 2 and 3). In particular, materials with a methylene blue adsorption capacity of 150 mmol / 100g or more exhibit high flexural strength.
[0057] (Examples 18-22, Comparative Examples 4-7) The ingredients and quantities (mass%) shown in Table 4 were placed in a Henschel mixer, an appropriate amount of water was added, and the mixture was stirred and mixed at 70-95°C. After further kneading with a three-roller at 30-70°C, the mixture was formed into thin rods using an extrusion molding machine to produce wire cores. After that, they were thoroughly dried to obtain red wooden colored pencil leads (water-soluble solid drawing material) with a length of 180 mm and a diameter of 3 mm.
[0058] The following water-soluble polymers were used. Polyvinyl alcohol; POVAL JP-05 (manufactured by Nippon Vinegar & Polyvinyl Alcohol Co., Ltd.) Polyethylene glycol; PEG #6000 (manufactured by NOF Corporation, average molecular weight: 8,800) Polyvinylpyrrolidone; Luvitec K-30 (manufactured by BASF Japan Ltd.)
[0059] The resulting water-soluble solid drawing material was subjected to measurements of its flexural strength after preparation, and the percentage change in flexural strength after being left for three weeks at a temperature of 40°C and a humidity of 60% RH was determined. Furthermore, the water solubility and writing feel of the resulting water-soluble solid drawing material were evaluated. The results are shown in Table 4 and Figure 2. Furthermore, the rate of change in bending strength in Example 6 was 36.5%.
[0060] [Table 4]
[0061] From the results in Table 4 and Figure 2, it can be seen that the water-soluble solid drawing materials of Examples 18-19, which contain a smectite-type clay mineral with a methylene blue adsorption capacity greater than 100 mmol / 100g and two types of water-soluble polymers, exhibit superior flexural strength, water solubility, and writing feel, and are superior to the water-soluble solid drawing material of Example 6, which contains one type of water-soluble polymer, in that the rate of change in flexural strength is smaller. Furthermore, it can be seen that the water-soluble solid drawing materials of Examples 21-22, which contain the smectite-type clay mineral and three types of water-soluble polymers, exhibit an even better rate of change in flexural strength. In contrast, the water-soluble solid drawing materials of Comparative Examples 4 and 5, which do not contain smectite-type clay minerals, exhibit insufficient bending strength and writing feel. Furthermore, the water-soluble solid drawing materials of Comparative Examples 6 and 7, which contain smectite-type clay minerals with a methylene blue adsorption amount of less than 100 mmol / 100g, exhibit poor water solubility. [Industrial applicability]
[0062] The water-soluble solid drawing material of the present invention has high bending strength, does not break or chip during drawing, and exhibits a smooth writing feel with excellent color application, making it suitable for a wide range of applications. Furthermore, the water-soluble solid drawing material of the present invention can maintain a low rate of change in bending strength even under high temperature and humidity conditions, thereby suppressing damage such as the tip of the drawing material crumbling during drawing, and not compromising the writing feel.
Claims
1. A water-soluble solid drawing material characterized by containing a smectite clay mineral having a methylene blue adsorption amount of more than 100 mmol / 100 g as measured by the JIS Z 2451:2019 6.3 colorimetric method, a colorant, a water-soluble polymer, and a surfactant.
2. 2. The water-soluble solid drawing material according to claim 1, wherein the smectite clay mineral is bentonite.
3. 3. The water-soluble solid drawing material according to claim 1, wherein the water-soluble polymer is at least one water-soluble polymer selected from the group consisting of polyvinyl alcohol and polyvinylpyrrolidone.
4. 4. The water-soluble solid drawing material according to claim 1, wherein the water-soluble polymer further comprises polyethylene glycol having an average molecular weight of 1,000 to 11,000.
5. 5. The water-soluble solid painting material according to claim 1, wherein the surfactant is at least one surfactant selected from the group consisting of fatty acid alkali metal salts and nonionic surfactants having an HLB value (Griffin method) of 10 or more and 20 or less.
6. 6. The water-soluble solid painting material according to claim 1, wherein the coloring material comprises a hiding pigment and a coloring pigment.
7. 7. The water-soluble solid painting material according to claim 1, further comprising a wax, said wax comprising a higher fatty acid and an oil or fat or an oil or fat derivative.